2014
DOI: 10.7717/peerj.328
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of insect pollinators to crop yield and quality varies with agricultural intensification

Abstract: Background. Up to 75% of crop species benefit at least to some degree from animal pollination for fruit or seed set and yield. However, basic information on the level of pollinator dependence and pollinator contribution to yield is lacking for many crops. Even less is known about how insect pollination affects crop quality. Given that habitat loss and agricultural intensification are known to decrease pollinator richness and abundance, there is a need to assess the consequences for different components of crop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
146
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 220 publications
(155 citation statements)
references
References 61 publications
6
146
1
2
Order By: Relevance
“…common), red clover ( Trifolium pratense ), and purple tansy ( Phacelia tanacetifolia ) as potential surrogate plants for semi-field pesticide studies with the common eastern bumble bee ( Bombus impatiens Cresson). We focussed on these plants because they are attractive to bumble bees (Williams, 1997; Carreck & Williams, 2002; Pontin et al, 2006; Jacquemart, Gillet & Cawoy, 2007; Colla & Dumesh, 2010; Bartomeus et al, 2014), and purple tansy has previously been used in semi-field studies with bees (Cabrera et al, 2016). Bombus impatiens is abundant throughout eastern Canada and United States, and currently is the only bumble bee available commercially for crop pollination in North America.…”
Section: Introductionmentioning
confidence: 99%
“…common), red clover ( Trifolium pratense ), and purple tansy ( Phacelia tanacetifolia ) as potential surrogate plants for semi-field pesticide studies with the common eastern bumble bee ( Bombus impatiens Cresson). We focussed on these plants because they are attractive to bumble bees (Williams, 1997; Carreck & Williams, 2002; Pontin et al, 2006; Jacquemart, Gillet & Cawoy, 2007; Colla & Dumesh, 2010; Bartomeus et al, 2014), and purple tansy has previously been used in semi-field studies with bees (Cabrera et al, 2016). Bombus impatiens is abundant throughout eastern Canada and United States, and currently is the only bumble bee available commercially for crop pollination in North America.…”
Section: Introductionmentioning
confidence: 99%
“…We analysed three separate datasets conducted in three crop systems (field beans, strawberries and spring oilseed rape) in UK, Germany and Sweden, respectively [26]. Bees were sampled in 10 fields in each crop type by hand-netting along a fixed transect.…”
Section: (I) Pollinationmentioning
confidence: 99%
“…cabbage and other brassicas, carrots, turnips, lettuce, chicory and onions) increases the quality of the seed production (Gallai and Vassière 2009). In addition, insect pollinators enhance fruit and seed quality Bartomeus et al 2014;Garratt et al 2014;Marini et al 2015;Saeed et al 2016) and reinforces pest management (Cross et al 2015) which constitutes an indirect and difficult benefit to measure, but extremely important for the agricultural market. Also, a recent study on pollination by wild insect pollinators has showed their capacity to increase the seed production in 41 agricultural systems globally, regardless of the abundance of honey bees .…”
Section: Introductionmentioning
confidence: 99%